2014
DOI: 10.1016/j.scitotenv.2013.12.095
|View full text |Cite
|
Sign up to set email alerts
|

The impact of climate change on the treatability of dissolved organic matter (DOM) in upland water supplies: A UK perspective

Abstract: Climate change in the UK is expected to cause increases in temperatures, altered precipitation patterns and more frequent and extreme weather events. In this review we discuss climate effects on dissolved organic matter (DOM), how altered DOM and water physico-chemical properties will affect treatment processes and assess the utility of techniques used to remove DOM and monitor water quality. A critical analysis of the literature has been undertaken with a focus on catchment drivers of DOM character, removal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
128
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(131 citation statements)
references
References 227 publications
3
128
0
Order By: Relevance
“…In addition, 304 algogenic DOC is reported to be associated with higher nitrogenous DBP (NDBP) production than 305 humic DOC (Bond et al 2011;Ritson et al 2014). Thus the relationship between DOC origin and THM 306 yield in drinking water is not straightforward.…”
Section: Xad-fractionation 168mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 304 algogenic DOC is reported to be associated with higher nitrogenous DBP (NDBP) production than 305 humic DOC (Bond et al 2011;Ritson et al 2014). Thus the relationship between DOC origin and THM 306 yield in drinking water is not straightforward.…”
Section: Xad-fractionation 168mentioning
confidence: 99%
“…Some species of algae also produce toxic metabolites which present a public 36 health risk (Ĺ˝egura et al 2011). The frequency and duration of algal blooms is predicted to increase 37 as a result of climate change (Ritson et al 2014). Thus, developing a better understanding of the 38 hydrophilic neutral (HPIN) according to their sequential adsorption onto macroporous resins; 130 Superlite™ DAX-8™ resin and Amberlite™ XAD-4™ resin (Sigma-Aldrich, Dorset, UK).…”
Section: Introduction 29mentioning
confidence: 99%
“…In addition to ecological impacts, high riverine nutrient concentrations can cause significant socio-economic implications by impairing freshwater ecosystem services including drinking water supply, recreational opportunities, and aesthetic qualities such as taste or odor [Millennium Ecosystem Assessment, 2005;Bennett et al, 2009]. Moreover, drinking water supplies with high concentrations of nitrate and disinfectant by-products (associated with the removal of aromatic dissolved organic matter) have been linked to adverse public health impacts including cancer, diabetes, and mutagenic diseases [Ward et al, 2005;Carpenter et al, 2013;Ritson et al, 2014]. Given the global relevance of increasing river nutrient concentrations, there is a critical need to develop a thorough mechanistic understanding of the variability and controls on nutrient mobilization and export from river catchments.…”
Section: Introductionmentioning
confidence: 99%
“…Chow et al [19] reported that significant amounts of DBP precursors in sub-surface waters can be attributed to the leaching of organics from deciduous litter of surrounding vegetation, emphasizing the influence of catchment sub-surface water on reservoir water quality and consequently on DBP formation. The concentration and character of DOM significantly influences raw and treated water quality and DBP formation [9,20,22].…”
Section: Introductionmentioning
confidence: 99%